MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA PROMOSI UNTUK MENINGKATKAN MINAT BELI KONSUMEN - Deru R Indika; Cindy Jovita (Jurnal Bisnis Terapan, 2017)
The speed of internet access and the rapid growth of the smartphone industrymakes it easier for people to get information. In the field of marketing, this affectshow the promotion is done. The use of social media which is actually meansfor social interaction between online individuals becomes commonly used bycompanies as a tool for promotion including in the tourism industry. One of thesocial media that is often used is Instagram, an application that allows users toshare photos and pictures along with short messages with other users. This studydiscussed how Instagram as a social media can affect consumer purchase intentiontoward a tourist destination. The subject of research is Floating Market located inLembang, Bandung, West Java. The results showed that information deliveredthrough Instagram was effective in increasing consumer purchase intention upto 50.2%